Coming to Grips-How Nurses Deal With Restlessness, Confusion, and Physical Restraints on a Neurological/Neurosurgical Ward - Jaco Tresfon; Kirsten Langeveld; Anja H. Brunsveld-Reinders; Jaap Hamming (SAGE Publishing, 2023)
Physical restraints are viewed as potentially dangerous objects for patient safety. Contemporary efforts mainly focus on preventing bad outcomes in restraint use, while little attention is paid under what circumstances physical restraints are applied harmlessly. The aim of this research was to understand how physical restraints are used by neurology/neurosurgery ward nurses in relation to the protocol. In ethnographic action research, the Functional Resonance Analysis Method (FRAM) was used to map and compare physical restraints as part of daily ward care against the protocol of physical restraints. Comparison between protocol and actual practice revealed that dealing with restlessness and confusion is a collective nursing skill vital in dealing with physical restraints, while the protocol failed to account for these aspects. Supporting and maintaining this skillset throughout this and similar nursing teams can prevent future misguided application physical restraints, offering valuable starting point in managing patient safety for these potentially dangerous objects.